The effect of heating rate on the sintering of agglomerated NaNbO3 powders - Leite, E. R.; Nobre, MAL; Ribeiro, M. D.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Kluwer Academic Publ, 1998)
The effect of heating rate on the sintering of agglomerated NaNbO3 powders, processed by the polymeric precursors method, was studied. The results showed that the presence of agglomerated powder leads to a heterogeneous microstructure, with bimodal grain size distribution, after sintering. Using a high heating rate, the sintering of agglomerated particles was inhibits, leading to a homogeneous microstructure, with single grain size distribution. (C) 1998 Kluwer Academic Publishers.